Mechanical Behavior of Hulled Peanut and Its Kernel During the Shelling Process - Ince, Ahmet; Ugurluay, Selçuk; Güzel, Emin; Özcan, M. Tunç (2009)
The rupture resistance of both hulled peanut and its kernel were examined in terms of average rupture force, deformation, firmness and toughness. Samples at various moisture contents and sizes were compressed at three loading positions (longitudinal, parallel to split plane and perpendicular to split plane). The compressive force needed to rupture for the hulled peanut and the kernel decreased with an increase in moisture content as the deformation at rupture point increased. Moreover, firmness increased and toughness decreased when moisture content increased. Larger size hulled peanut and kernel had higher rupture force and firmness values. For toughness, the trend was opposite. The highest values of firmness and toughness were measured at perpendicular loading position to the split plane. The over all average values of rupture force, deformation, firmness and toughness for hulled peanut and kernel when the samples were compressed, in relation to the over all range of moisture content, size and loading position, were determined as 87.58 and 47.45 N, 2.16 and 1.46 mm, 46.80 and 49.40 N mm -1, 0.018 and 0.024 mJ mm -3, respectively.
Keywords: Peanuts; Postharvest handling